Brain abscess as an otorhinolaryngological complication - Miguel Hernández; Mildred P. Zambrano Leal (Sociedad Ecuatoriana de Pediatría (Núcleo de Quito), 2023)
Introduction: A brain abscess is a fatal infection if it is not diagnosed and treated promptly. It is more common in children and has high mortality rates compared to adults. Respiratory infections, such as otitis and sinusitis, generally precede brain abscesses. In most cases, a double treatment, antibiotics, and surgery should be necessary. Complications can be fatal even with proper treatment. Clinical case: This is a 3-year-old girl patient with a history of respiratory infection. His parents took him to the emergency room due to a severe headache and a seizure episode. The clinical examination revealed left ear otalgia associated with pain and sensitivity to palpation of the mastoid region. Laboratory tests revealed leukocytosis of 18,770/MMC with neutrophilia, thrombocytosis of 628,000/MMC, elevated C-reactive protein of 8.35 mg/dl (average value 0.10-0.30 mg/dl) and elevated ferritin of 250.20 ng/dl (average value 7-140 ng/dl). Due to the history and clinical findings, a computed tomography of the skull was performed, revealing an image of evident hypodensity of the left hemisphere. An MRI was also performed, which revealed the lesion previously associated with thrombosis of the left breast. He received antibiotics and low molecular weight heparin with neurosurgery therapy, with good results. Evolution: Despite the extent of the injury, he had two episodes of seizures. He promptly received adequate antibiotic therapy and surgical treatment with good results. Three months later, for follow-up, he looks normal and has no long-term complications. Conclusions: Complications of brain abscess, even with adequate treatment, can be severe, such as epilepsy or death.